Evalvacija pouka književnosti v gimnaziji ali paberki nekdanjega profesorja slovenščine na ŠKG v Šentvidu - Kurinčič, Jože (Jezik in slovstvo, 2019)
The article reports on the internal evaluation of literature teaching that took place in 2015 and 2016 at the Diocesan Classical Grammar School in Šentvid, Ljubljana. The aim was to reflect on the positive and negative aspects of the secondary school literature curriculum, and above all to consider how it could be improved. The focus was on how appropriate the selected literary texts are to the age and understanding of the adolescent, the degree to which they take into account the principle of proximity (not only psychological, but also local), the place of "Catholic" authors and religious topics in the curriculum and textbooks, and which values can be communicated by a specific text.
Keywords: estetske vrednote; etične vrednote; evalvacija; gimnazije; katoliški avtorji; pouk književnosti; slovenski avtorji; spoznavne vrednote; učni načrti; verska tematika